Efektivitas Model TTW (Think Talk Write) terhadap Kemampuan Literasi dan Numerasi Dasar Siswa - Dyah Indraswati; Asri Fauzi; Ilham Syahrul Jiwandono; Aisa Nikmah Rahmatih (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2022)
The purpose of this study was to determine the effectiveness of the TTW (Think Talk Write) learning model on the basic literacy and numeracy abilities of VB class students at SDN Tanak Embang, Selebung, Batukliang, Lombok Tengah, Nusa Tenggara Barat. This research is quantitative research using pre-experimental design method type one group pretest-posttest. This research is a population study because all 21 students in class VB are the research subjects. The instruments in this study were 10 multiple choice questions which were used as questions for students' pretest and posttest. The data analysis technique used a normality test as a prerequisite for analysis, paired sample t-test, an effect size test, and N-Gain test. The normality test shows that all data are normally distributed. The paired sample t-test showed a difference between the pretest and posttest scores, where the posttest scores were better than the pretest scores. The effect size test shows that the score d=-1,445 is in a small category because it is 0.05. This means that the TTW (Think Talk Write) learning model has a small effect on students' basic literacy and numeracy skills. The N-Gain test shows the average N-gain score for class VB is 47.0805 or 47% is included in the less effective category. Thus, it can be concluded that the use of the TWW (Think Talk Write) learning model is less effective in improving the basic literacy and numeracy skills of class VB students at SDN Tanak Embang.